Impact behavior of recycled aggregate concrete modified with nano-silica and fiber - Xingguo Wang; Zhixuan Liu; Yonggui Wang; Xianggang Zhang; Maolin Jiang (Scientific Reports)
Abstract This study proposes a multidimensional reinforcement framework integrating three mechanisms: nano-silica (SiO2) interfacial reconfiguration, fiber toughening, and dynamic response regulation. The effects of pre-soaking recycled aggregates in nano-SiO2 solutions at concentrations of 0%, 1.0%, and 2.0% and incorporating steel fibers (0%, 1.0%, 2.0%) or polyvinyl alcohol (PVA) fibers (0%, 0.1%, 0.2%) into recycled aggregate concrete (RAC). The impact resistance of treated specimens was evaluated under different strain rates using the split Hopkinson pressure bar (SHPB) method. Fracture patterns were analyzed, and dynamic stress-strain relationships were examined to assess the evolution of dynamic compressive strength and dynamic growth factor. Results indicated that higher impact velocities led to greater specimen damage, while increased nano-SiO2 concentrations and fiber reinforcement enhanced structural integrity. Pre-treatment with nano-SiO2 accelerated the peak stress occurrence in the dynamic stress-strain response, whereas fiber incorporation substantially increased peak stress. Both dynamic compressive strength and dynamic growth factor exhibited a linear relationship with strain rate, suggesting that nano-SiO2 and steel fibers collectively enhanced impact resistance.The application of RAC in protective engineering relies on nanoscale pretreatment and fiber reinforcement technologies to enhance the recycling of construction and demolition waste (CDW), enabling its conversion into high-value applications.